Atypical Response of B-1 Cells to BCR Ligation: A Speculative Model - Holodick, Nichol E.; Rothstein, Thomas L. (Frontiers in Immunology, 2013)
Peritoneal B-1a cells manifest unusual signaling characteristics that distinguish them from splenic B-2 cells. These include the failure of BCR engagement to trigger NF-κB activation and DNA replication. Despite extensive study, a clear explanation for these characteristics has not emerged. Here we aim to develop a unified paradigm based on previous reports and recent results, which proposes a central role for phosphatase activity. We hypothesize B-1a cells are unable to induce NF-κB or proliferate after BCR cross-linking due to increased phosphatase abundance or activity. This phosphatase abundance and/or activity may be the result of unique B-1a cell characteristics such as increased levels of HSP70 and/or constitutive secretion of IL-10. We speculate that phosphatase activity cannot be overcome by BCR ligation alone due to insufficient Vav protein expression, which does not allow for proper production of ROS that inhibit phosphatases. Furthermore, constitutively active Lyn also plays a negative regulatory role in B-1a. We expect that a new focus on phosphatase activity and its suppression will be revealing for BCR signal transduction in B-1 cells.